2017
DOI: 10.1016/j.jvir.2016.12.698
|View full text |Cite
|
Sign up to set email alerts
|

A prospective, double-blind, randomized controlled study evaluating the effects of two new IV medications, IV acetaminophen and/or IV ibuprofen, on standard of care pain and antiemetic management in uterine fibroid embolization patients

Abstract: No. 102 Uterine artery embolization followed by elective myomectomy for the treatment of intracavitary fibroids: preliminary experience

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…Using IV acetaminophen and combining it with IV ibuprofen, Chaabane et al 13 showed that less opioid medication was used in comparison to the group prescribed IV ketorolac only. The authors suggest a benefit to the combination treatment, as the early data demonstrated a trend toward less opioid usage with better pain control.…”
Section: Acetaminophenmentioning
confidence: 99%
See 1 more Smart Citation
“…Using IV acetaminophen and combining it with IV ibuprofen, Chaabane et al 13 showed that less opioid medication was used in comparison to the group prescribed IV ketorolac only. The authors suggest a benefit to the combination treatment, as the early data demonstrated a trend toward less opioid usage with better pain control.…”
Section: Acetaminophenmentioning
confidence: 99%
“…23 Other common opiates used for UAE are hydromorphone, morphine, and fentanyl and/or acetaminophen with either hydrocodone or oxycodone. 3,11,[13][14][15] Saibudeen et al 24 suggested that although there were mildly better pain scores in patients receiving opioids, NSAIDs, and acetaminophen, these were not statistically significant.…”
Section: Opioidsmentioning
confidence: 99%